ANALISIS PENGARUH RASIO CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING FINANCING (NPF), FINANCING TO DEPOSIT RATIO (FDR), DAN RASIO EFISIENSI OPERASIONAL (REO) TERHADAP RETURN ON EQUITY (ROE) BANK UMUM SYARIAH DI INDONESIA (PERIODE 2010-2014) - Dini, Navrida Rahma; S.E., M.M., Prihatiningsih (Jurnal Sains Ekonomi dan Perbankan Syariah, 2015)
AbstractThis study purpose to analyze the influence of the ratio of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operational Efficiency Ratio (OER) to Return On Equity (ROE) Islamic Banks in Indonesia (Period 2010-2014) partially and simultaneously.Results of this study concluded that based on the results of statistical F test simultaneously variables of CAR, NPF, FDR, and REO have significant impact toward ROE, based on the statistical t-test variable of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and the Efficiency Ratio Operations (OER) have negative and significant impact, whereas Financing to Deposit Ratio (FDR) has positive and significant impact on Return On Equity (ROE) Islamic Banks in Indonesia in 2010-2015.Keywords:Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operational Efficiency Ratio (OER), and Return On Equity (ROE).